Perkembangan Bahasa dan Sastra Arab di Berbagai Negara (Mesir, India dan Indonesia Lama) - Muhammad Yasin; Syarifuddin Ondeng; Andi Abdul Hamzah (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2024)
This study aims to find out how the development of Arabic language and literature in Egypt, India and old Indonesia. This research is a qualitative descriptive library research, with a historical approach. The problems discussed in this study are first: how the rise of Modern Arabic literature in Egypt, second: how the development of Arabic language and literature in India, and third: what are the influences of Arabic literature on old Indonesian literature. The results showed that: (1) The rise of Arabic literature in Egypt was influenced by several factors, including: Al-Madaris (Schools), Al-Mathba'ah (Printing), Ash-Shuhuf / Al-Jaro'id (Newspapers), and Tarjamah. Pioneer of the neoclassical school of Arabic poetry. (2) The history of Arabic language and literature in India began when the Arabs entered India as traders, preachers, and conquerors. The existence of the Arabic language became strong and widespread when Islam came. Arabic language and literature grew and developed gradually in different parts of the Indian subcontinent, especially under Islamic dynasties. Period after period gave rise to scholars and literati who had an important influence on Arabic language and literature. (3) Based on the comparative analysis of literature above, it is evident that Indonesian literature in certain phases precisely before the 20th century was influenced by Arabic literature. Hamzah Fansuri, who is considered a pioneer of Malay literature or classical Indonesian literature in his Sufi poetry proved to be heavily influenced by Arabic literature.